Asymptotic behavior for a nonlinear viscoelastic problem with a velocity-dependent material density - Nasser-Eddine Tatar (International Journal of Mathematics and Mathematical Sciences)
We consider a nonlinear viscoelastic problem and prove that the solutions are uniformly bounded and decay exponentially to zero as time goes to infinity. This is established under weaker conditions on the relaxation function than the usually used ones. In particular, we remove the assumptions on the derivative of the kernel. In fact, our kernels are not necessarily differentiable.